Underground gas storage : worldwide experiences and future development in the UK and Europe - Evans, D. J.; Chadwick, R. A. (Geological Society, 2009)
In October 2004, the Geological Society convened a two-day conference at the Aberdeen Conference Centre: 'The Future Development and Requirements for Underground Gas Storage in the UK and Europe'. The conference was held at a time when attention was turning to the imminent import dependency facing the UK and was attended by representatives from not only industry and academia, but also local government departments who were dealing with applications to develop underground gas storage (UGS) facilities onshore UK. This volume arose from the 2004 Aberdeen meeting. In the present gas and energy supply climate, this review and appraisal of the technologies of underground gas storage and future UK requirements is particularly timely.
Keywords: Natural gas -- Underground storage.; Natural gas -- Underground storage -- Great Britain.; Natural gas -- Underground storage -- Europe.; elektronické knihy; electronic books